Regioselective Addition of Quinoline Derivatives to Carbonyl Compounds via Palladium-Catalyzed Umpolung with Diethylzinc - Matsumoto, Yohei; Yamamoto, Kosuke; Kuriyama, Masami; Nishida, Koyo; Onomura, Osamu (Synthesis, 2019)
An efficient method for the C-4-selective addition of quinoline derivatives to carbonyl compounds is described. The combination of 2-ethoxy-1-ethoxycarbonyl-1,2-dihydroquinolines (EEDQs) with a palladium catalyst and diethylzinc generates nucleophilic allyl species which undergo addition to various aldehydes and ketones. C-4-Substituted quinoline derivatives are obtained in high to excellent yields with moderate diastereoselectivities.
Keywords: palladium catalysis; diethylzinc; Umpolung; dihydroquinoline; regioselectivity